1988
DOI: 10.1093/ajcp/89.6.764
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Analysis of DNA Content in Hürthle Cell Adenomas and Carcinomas of the Thyroid

Abstract: Paraffin-embedded surgical biopsy material from 17 Hürthle cell tumors of the thyroid was examined for DNA content by flow cytometry to assess the diagnostic and prognostic utility of ploidy determinations in these rare tumors. Both adenomas (11 cases) and carcinomas (6 cases) were studied. As a control for methods, ten randomly selected normal autopsy thyroids were analyzed, all of which demonstrated normal diploid DNA content. Among the Hürthle cell tumors, however, aneuploid peaks were present in six adenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 0 publications
2
16
0
2
Order By: Relevance
“…17,25,[44][45][46][47][48]52,66,68,69,77 Some of the earlier morphometric studies, which found significant differences in nuclear features between follicular adenomas and follicular carcinomas, may have included cases of the follicular variant of papillary carcinoma, an entity that has become generally accepted only more recently. A similar lack of discrimination was found in DNA quantitation studies, which have shown a large overlap in aneuploidy rates between Hürthle cell adenomas and carcinomas 6,9,11,67,81 as well as between follicular adenomas and carcinomas. 81 The results of this study, together with the recent promising results obtained with argyrophilic nucleolar organizer regions quantitation in follicular neoplasms 16,38,63,71 may indicate that more diagnostic information can be gained by careful study of the number, size and shape of the nucleoli than from such features such as nuclear size, variation in nuclear size, nuclear irregularity and nucleocytoplasmic ratio, which have traditionally received more attention.…”
supporting
confidence: 69%
“…17,25,[44][45][46][47][48]52,66,68,69,77 Some of the earlier morphometric studies, which found significant differences in nuclear features between follicular adenomas and follicular carcinomas, may have included cases of the follicular variant of papillary carcinoma, an entity that has become generally accepted only more recently. A similar lack of discrimination was found in DNA quantitation studies, which have shown a large overlap in aneuploidy rates between Hürthle cell adenomas and carcinomas 6,9,11,67,81 as well as between follicular adenomas and carcinomas. 81 The results of this study, together with the recent promising results obtained with argyrophilic nucleolar organizer regions quantitation in follicular neoplasms 16,38,63,71 may indicate that more diagnostic information can be gained by careful study of the number, size and shape of the nucleoli than from such features such as nuclear size, variation in nuclear size, nuclear irregularity and nucleocytoplasmic ratio, which have traditionally received more attention.…”
supporting
confidence: 69%
“…The same is true of the aneuploid DNA content, which appears to be common to benign and malignant Hürthle cell and to oxyphilic cell tumours in the different settings [5,48,60].…”
Section: Light and Electron Microscopymentioning
confidence: 90%
“…Diploid nuclear DNA content is associated with a benign clinical course, even when other criteria for malignancy are present. 116,[127][128][129][130] The role of FNA biopsy in establishing the diagnosis of Hurthle cell lesions has been addressed in a number of studies. 118,125,131 In summary, these all show that the distinction between benign and malignant Hurthle cell neoplasms based on cytopathology alone probably cannot be made with a high degree of accuracy.…”
Section: Diagnosismentioning
confidence: 99%